Integrin-Linked Kinase Expression Characterizes the Immunosuppressive Tumor Microenvironment in Colorectal Cancer and Regulates PD-L1 Expression and Immune Cell Cytotoxicity - Almasabi, Saleh; Boyd, Richard; Ahmed, Afsar U.; Williams, Bryan R. G. (Frontiers in Oncology, 2022)
Integrin-linked kinase (ILK) has been implicated as a molecular driver and mediator in both inflammation and tumorigenesis of the colon. However, a role for ILK in the tumor microenvironment (TME) and immune evasion has not been investigated. Here, we show a correlation of ILK expression with the immunosuppressive TME and cancer prognosis. We also uncover a role for ILK in the regulation of programmed death-ligand 1 (PD-L1) expression and immune cell cytotoxicity. Interrogation of web-based data-mining platforms, showed upregulation of ILK expression in tumors and adjacent-non tumor tissue of colorectal cancer (CRC) associated with poor survival and advanced stages. ILK expression was correlated with cancer-associated fibroblast (CAFs) and immunosuppressive cell infiltration including regulatory T cells (Treg) and M2 macrophages (M2) in addition to their gene markers. ILK expression was also significantly correlated with the expression of different cytokines and chemokines. ILK expression showed pronounced association with different important immune checkpoints including PD-L1. Deletion of the ILK gene in PD-L1 positive CRC cell lines using a doxycycline inducible-CRISPR/Cas9, resulted in suppression of both the basal and IFNγ-induced PD-L1 expression via downregulating NF-κB p65. This subsequently sensitized the CRC cells to NK92 immune cell cytotoxicity. These findings suggest that ILK can be used as a biomarker for prognosis and immune cell infiltration in colon cancer. Moreover, ILK could provide a therapeutic target to prevent immune evasion mediated by the expression of PD-L1.